Institutions and transition: does a better institutional environment make water users associations more effective in Central Asia? - Gunchinmaa, Tumur; Yakubov, Murat (IWA Publishing, 2010)
Integrated water resource management (IWRM) is a widely recognized management framework that is currently being adopted throughout post-Soviet Central Asia to inform and guide national water sector reforms, and to keep up with the pace of the faster moving land reforms taking place in the region. With hydrographic principles and public participation being at the core of this framework, the process in the region has started with the reform of on-farm irrigation systems by creating water users associations (WUAs), transferring irrigation management to them and introducing irrigation service fees. This paper draws on the experiences, over four years, of three study WUAs set up in the Ferghana Valley in Uzbekistan, Tajikistan and the Kyrgyz Republic. Aiming to explore the differences in institutional environment and arrangements in these three countries for establishing WUAs, as well as assessing WUA performances (particularly from users' perspectives), the study reveals that it is not only the newly-established institutional arrangements in the irrigation sector but also their internal operations, coupled with other important factors such as size of area farmed, overall viability of agriculture and a wider economic context that crucially determine overall irrigation performance.